PENGARUH MODEL DAN CARA PENILAIAN TERHADAP HASIL BELAJAR IPA DENGAN MENGONTROL PENGETAHUAN AWAL MATEMATIKA SISWA - Adam Rumbalifar (Jurnal Evaluasi Pendidikan, 2018)
This research aims to study the effect of models and how to assess toward science achievement by controlling previous knowledge mathematics of students. This study conducted at SMP Negeri 1, SMP Negeri 2, and SMP Negeri 3 Bula East Seram district with a population of 295 students. This study used a quasi-experimental method 2 X 3 factorial design using the cell mean univariate models with model covariates Analysis (ANCOVA) which variables are: (1) the dependent variable or response variable and (2) the independent variable. The results by controlling previous mathematics of students obtained: (1) the science achievement of students who were given a written test assessment models is higher than the group given peer assessment model, (2) science group of students who were given a written test assessment models is higher than the a given model of self-assessment, (3) science achievement of students who were given the peer assessment model is higher than the group given the self-assessment models, (4) science achievement of students who are given the analytical assessment method is higher than the group given the way holistic assessment, (5) there is interaction between asses models by way of assessment of science achievement, (6) special group of students who were given an analytical assessment methods, achievement assessment model of science written test is higher than the inter theme asses models, (7) special groups of students were given an analytical assessment methods, achievement assessment model of science written test is higher than the self-assessment models, (8) a special group of students who were given an analytic way of assessment of achievement assessment model of science higher peer self-assessment model, (9) specific groups of students were given ways holistic assessment of achievement assessment model of science written test is higher than the peer assessment model, (10) a special group of students who were way holistic assessment of achievement assessment model of science written test is higher than the self-assessment models, (11) special groups of students were given ways holistic assessment of achievement assessment model of science higher peer self-assessment model, (12) a special group of students who use the model written assessment of achievement assessment models of science analytic way higher than holistic assessment method, (13) specific groups of students using peer asses model of achievement assessment models of science analytic way higher than holistic assessment method, and (14) special groups of students who use the self-assessment model of science achievement assessment means higher analytic holistic assessment of the way.